Robotic sample changers for macromolecular X‐ray crystallography and biological small‐angle X‐ray scattering at the National Synchrotron Light Source II. Corrigendum. (23rd December 2021) - Lazo, Edwin O.; Antonelli, Stephen; Aishima, Jun; Bernstein, Herbert J.; Bhogadi, Dileep; Fuchs, Martin R.; Guichard, Nicolas; McSweeney, Sean; Myers, Stuart; Qian, Kun; Schneider, Dieter; Shea-McCarthy, Grace; et al.
Abstract : A correction in the paper by Lazo et al. [(2021). J. Synchrotron Rad. 28, 1649–1661 ] is made. Abstract : A correction in the paper by Lazo et al. [(2021). J. Synchrotron Rad. 28, 1649–1661 ] is made.